Novel and potential future therapeutic options in systemic autoimmune diseases - Balogh, Lili; Oláh, Katalin; Sánta, Soma; Majerhoffer, Nóra; Németh, Tamás (Frontiers in Immunology, 2024)
Autoimmune inflammation is caused by the loss of tolerance to specific self antigens and can result in organ-specific or systemic disorders. Systemic autoimmune diseases affect a significant portion of the population with an increasing rate of incidence, meaning that is essential to have effective therapies to control these chronic disorders. Unfortunately, several patients with systemic autoimmune diseases do not respond at all, or just partially to available conventional synthetic disease-modifying drugs and targeted therapies. However, there is some light at the end of the tunnel as during the past few years, some new medications have been approved and can be used in real life clinical settings. Meanwhile, several new drug candidates arrived to the horizon offering promising novel treatment options. Here, we summarize the newly available medications and the most encouraging drug candidates in rheumatoid arthritis, in systemic lupus erythematosus, in Sjögren’s disease, in systemic sclerosis, in systemic vasculitis and in autoimmune myositis.